Chatbot Bagi Siswa Program Keahlian Otomatisasi dan Tata Kelola Perkantoran - Alienra Davry Nanda Kadun MT; Roland Everson Binur (Lembaga Pengembangan Kinerja Dosen, 2024)
As technology advances, the presence of Artificial Intelligence / AI is no longer inevitable. One of the functions of AI that supports human work is the educational AI. ChatGPT is a conversational AI that forms sentences based on the information given to it. This AI can be used by all groups, especially students when they need instant, systematic and customized information. Office administration students of SMKS YPKP Jayapura are the target group of this community service program. We hoped that students could gain knowledge about ChatGPT, especially we wanted to improve students' skills in using technology.